2018
DOI: 10.1155/2018/7328128
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-Related Distress Assessment among Type 2 Diabetes Patients

Abstract: Background and Objectives Diabetes is one of the most common chronic diseases; it is a debilitating and hard to live with. Diabetes-related distress (DRD) refers to the emotional and behavioral changes caused by diabetes. Our study aims to assess the prevalence of DRD among type 2 diabetes (T2D) patients using Diabetes Distress Scale-17 items (DDS-17) and its relation to complications and treatment modalities. Methods A cross-sectional study of adult T2D patients with follow-up visits at the Diabetes and Endoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
70
5
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(109 citation statements)
references
References 23 publications
(44 reference statements)
15
70
5
10
Order By: Relevance
“…The results of the present study are consistent with those of Zhou et al, which reported that the total DDS score was not significantly related to patients' gender, age, diabetes duration, diabetes education, or complications [38]. On the other hand, other studies have reported that DRD is associated with age, duration of diabetes, occupation, marital status, glycemic status, treatment modalities, comorbidity, and diabetic complications [25,41,42]. These findings suggest that there may be other factors which affect DRD, e.g., type of diabetes, treatment regimen, and socioeconomic factors [21].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the present study are consistent with those of Zhou et al, which reported that the total DDS score was not significantly related to patients' gender, age, diabetes duration, diabetes education, or complications [38]. On the other hand, other studies have reported that DRD is associated with age, duration of diabetes, occupation, marital status, glycemic status, treatment modalities, comorbidity, and diabetic complications [25,41,42]. These findings suggest that there may be other factors which affect DRD, e.g., type of diabetes, treatment regimen, and socioeconomic factors [21].…”
Section: Discussionsupporting
confidence: 91%
“…However, another German study conducted at the primary care level reported only a 1.2% prevalence of DRD using the PAID scale [39,40]. The differences in DRD prevalence might result from differences in the assessment tools, i.e., the PAID and the DDS-17 questionnaires, which could potentially affect prevalence, e.g., sample size, access to health care, care setting [39], and demographic variables, e.g., education level and family support, as well as health status, e.g., HbA1c level, and co-morbidity [24,41,42]. The findings of these studies are consistent with our finding that DRD prevalence is higher in people with type 2 diabetes treated in a secondary and tertiary care setting than in those treated in a primary care setting [39,43].…”
Section: Discussionmentioning
confidence: 99%
“…It was noted that those who had high levels of DDS had poor glycemic control. Similar finding was also observed in other populations (Islam et al, 2013;Kuniss et al, 2017;Aljuaid et al, 2018). Diabetes related distress generally shows a closer association with glycemic control.…”
Section: Discussionsupporting
confidence: 89%
“…The present study highlighted that 22.5% of men and about 55% of women were screened positive for moderate to high DRD on a DDS-17 scale. Another study using DDS-17 total scores (Aljuaid et al, 2018) also reported that T2DM subjects were more likely to have DRD especially women when they belonged to the low income, unemployed or had any diabetes complications. Similar results were also observed in our study which indicated high levels of diabetes distress in women.…”
Section: Discussionmentioning
confidence: 95%
“…In Japan, the prevalence of type 2 diabetes mellitus (T2DM) continues to rise, largely owing to the aging population 3 and lifestyle factors, such as sedentary behavior and obesity associated with westernization 4,5 . Left untreated, T2DM can have lifethreatening consequences, placing a substantial cost burden on healthcare systems [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%